ショウワキチ ニ オケル ウチュウセン シンチレーション ノ ケンキュウ 1 - 北村, 正亟; キタムラ, マサトシ; 池上, 比呂志; イケガミ, ヒロシ; 小玉, 正弘; コダマ, マサヒロ; KITAMURA, Masatoshi; IKEGAMI, Hiroshi; KODAMA, Masahiro (国立極地研究所, 1975)
P(論文) Using 5-minute data of cosmic-ray neutron and meson intensities observed at Syowa Station, Antarctica in July and December 1970, short term variations covering the periods from 10 to 120 minutes have been investigated by a tool of sonagraph-type analyzer, in terms of enhancements in spectral power density as a function of time. Dynamic spectra thereby deduced show that there occurred, for the neutron component alone, seven times the enhanced cosmic-ray scintillations (called ECS) which exhibit the period of a few ten minutes with the persistent time from a few hours to one day. It is also shown that ECS events are not related to solar-terrestrial phenomena but to atmospheric pressure and wind velocity disturbances in the upper atmosphere. The presently observed ECS events are not of the extra-terrestrial origin but of the atmospheric origin. departmental bulletin paper